PELAKSANAAN PENINGKATAN STATUS HAK GUNA BANGUNAN YANG MASA BERLAKUNYA BERAKHIR MENJADI HAK MILIK DI PERUMNAS III KOTA PONTIANAK - NOVA RIZKY INNAYA NIM. A1011191186 (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACTSince a long time ago, the residential and settlement land purchased still has the status of building use rights because it is still under the control of the developer or PT, Perumnas is not allowed to own land in the form of property rights. Afterbuying and selling and renaming transactions, not a few have not improved their land status due to ignorance of the terms and procedures for upgrading, the process of upgrading rights that takes a long time, and large enough costs so that homeowners choose to postpone the increase in land rights until the validity period of their building use rights expires. Having a validity period of up to 20 years, land with the status of building use rights whose validity period expires can be upgraded to property rights with extension of rights or renewal of rights. Therefore, the purpose of writing this thesis entitled